Field Performance of Fruit-Waste Eco-Enzyme Baits for Trapping Bactrocera Spp. In Chili (Capsicum Frutescens L.) Fields of Tomohon City, Indonesia - Wanta, Noni N.; Paruntu, Meisye H. B.; Krisen, Jeane (Jurnal Agroekoteknologi Terapan (JAT), 2026)
Eco-enzyme (EE) liquids produced by fermenting fruit waste may provide low-cost, locally available odor sources for fruit-fly monitoring. This study evaluated the effectiveness of EE baits prepared from nutmeg, banana, and pineapple wastes, as well as a mixed formulation, for trapping Bactrocera spp. in chili (Capsicum frutescens L.) fields in Kakaskasen I Village, Tomohon City, Indonesia. The experiment used a randomized complete block design with four EE treatments and five replicates. Traps were installed in fruiting-stage chili plots at approximately 1.5 m above ground level with ~5 m spacing and were observed over four sampling rounds at 6-day intervals. Captured adult fruit flies were counted and identified morphologically, and treatment effects were analyzed using analysis of variance followed by an LSD (BNT) test at the 5% significance level. Two species were recorded, Bactrocera dorsalis and B. cucurbitae. Mean trap catches (adults per trap) were highest for pineapple EE (6.3), followed by mixed EE (3.1), nutmeg EE (1.7), and banana EE (1.3). Pineapple EE differed significantly from the other treatments (LSD5% = 3.7), whereas the remaining treatments did not differ significantly. Captures were reported to be predominantly female, and non-target insects were also collected, indicating limited selectivity. Overall, pineapple fruit-waste EE showed the strongest field performance and warrants further development as a practical bait for Bactrocera spp. monitoring in chili agroecosystems. Keywords: Bactrocera dorsalis, Capsicum frutescens, eco-enzyme, fermented fruit waste, food-baited trapping